Unusual case of failure to thrive: Type III Bartter syndrome - Agrawal, Sumit; Subedi, Krishnahari; Ray, Pankaj; Rayamajhi, Ajit (Journal of Nepal Health Research Council, 2017)
Bartter syndrome Type III is a rare autosomal recessive disorder resulting from an inherited defect in the thick ascending limb of the loop of henle of the nephrons in kidney. The typical clinical manifestations in childhood are failure tothrive and recurrent episodes of vomiting. Typical laboratory findings which help in the diagnosis are hypokalemic metabolic alkalosis, hypomagnesemia and hypercalciuria. We report a case of Type III Bartter syndrome not responding to repeated conventional treatment of failure to thrive.Keywords: Bartter syndrome; failure to thrive; hypercalciuria; hypomagnesemia; hypokalemia